Reimagining Democratic Societies : a new era of personal and social responsibility - Bergan, Sjur; Harkavy, Ira; Land, Hilligje van't. (Strasbourg : Council of Europe, 2013)
Reimagining democratic societies, although a demanding task, is one in which higher education must engage. As societies change, our understanding of democracy must also evolve. We need democratic institutions, but also democratic culture and democratic innovation. Citizen participation, as a cornerstone of democracy, must go beyond citizen mobilisation on just a few issues. An educated, committed citizenry deeply involved in creating and sustaining diverse democratic societies is essential for human progress and advancing the quality of life for all.The authors - academics, policy makers and practitioners from Europe and the United States - argue this point, making the case for why democratic reimagination and innovation cannot succeed without higher education and why higher education cannot fulfil its educational, academic and societal missions without working for the common good. Case studies provide examples of how higher education can contribute to reimagining and reinvigorating democracy.
Bibliografija na kraju svakog poglavlja.
Kazalo
Keywords: visokoškolsko obrazovanje -- društveni akteri -- društvena odgovornost -- demokratska društva